2022
DOI: 10.1002/mma.8226
|View full text |Cite
|
Sign up to set email alerts
|

Stability and bifurcation analysis of a fractional‐order model of cell‐to‐cell spread of HIV‐1 with a discrete time delay

Abstract: In this manuscript, fractional order is introduced onto a time‐delay differential equation model of cell‐to‐cell spread of HIV‐1. The fractional derivative of Caputo type is considered. We deal with the local stability of the resulting system and derive some necessary and sufficient conditions ensuring Hopf bifurcation to occur for this system. Explicit expressions for determining stability of critical surfaces are also given. An Adams‐type predictor–corrector technique is applied to illustrate the numerical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Mathematical modeling approach research done by scholars using a deterministic method [10,14], a stochastic method [7,22], or a fractional order method [23][24][25][26][27][28][29][30][31][32] has made a great contribution to linking the scientific approach with real-world physical situations and also for the decision-making process for solving real-world problems [33]. Different scholars have formulated and analyzed mathematical models on COVID-19 transmission [7, 8, 22, 24-26, 29, 30, 34-37], syphilis transmission [10,[17][18][19]23], and other infectious diseases transmission [20, 21,27,28,33,[38][39][40]; however, no one has done analysis on COVID-19 and syphilis co-infection transmission dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical modeling approach research done by scholars using a deterministic method [10,14], a stochastic method [7,22], or a fractional order method [23][24][25][26][27][28][29][30][31][32] has made a great contribution to linking the scientific approach with real-world physical situations and also for the decision-making process for solving real-world problems [33]. Different scholars have formulated and analyzed mathematical models on COVID-19 transmission [7, 8, 22, 24-26, 29, 30, 34-37], syphilis transmission [10,[17][18][19]23], and other infectious diseases transmission [20, 21,27,28,33,[38][39][40]; however, no one has done analysis on COVID-19 and syphilis co-infection transmission dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the governmental action and the individuals' risk awareness reduce effectively the infection spread. Different other types of fractional-order epidemic systems with delays were considered in earlier studies [3,6,13,[34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical models are mainly used in virology to understand how viruses spread within a host and how the disease develops. In the literature, there are several HBV infection models [6][7][8] that explain the dynamics of the disease from various perspectives. For example, Nowak et al [9] proposed a mathematical model on viral dynamics in 1996, which is called the "basic model" of virus dynamics, considering susceptible cells, infected cells, and viruses.…”
Section: Introductionmentioning
confidence: 99%